Analisis Pengelolaan Dana Zis Dalam Pemberdayaan Usaha Mikro Pada Baznas Kabupaten Magelang - Virinta Hasna Salsabila; Muhamad Wahyudi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
BAZNAS Kabupaten Magelang is an institution that manages zakat, infaq, and sadaqah (ZIS) funds to improve community welfare through micro-enterprise empowerment programs. This study aims to analyze the management of ZIS funds in micro-enterprise empowerment at BAZNAS Kabupaten Magelang. The research method used is qualitative with a case study approach through interviews, observations, and documentation. The results show that the management of ZIS funds has been implemented in accordance with established procedures; however, there are still obstacles in mentoring and monitoring the development of beneficiaries' businesses. Therefore, it is necessary to enhance supervision and optimize the use of technology to improve the effectiveness and accuracy of ZIS fund management.